2014
DOI: 10.1111/prd.12013
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive and acute periodontal diseases

Abstract: Inflammatory periodontal diseases are highly prevalent, although most of these diseases develop and progress slowly, often unnoticed by the affected individual. However, a subgroup of these diseases include aggressive and acute forms that have a relatively low prevalence but show a rapid-course, high rate of progression leading to severe destruction of the periodontal tissues, or cause systemic symptoms that often require urgent attention from healthcare providers. Aggressive periodontitis is an early-onset, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 25 publications
2
72
0
8
Order By: Relevance
“…come un coadiuvante della terapia meccanica; risulta ingiustificata nel trattamento delle forme croniche [9,10] . Anche per alcune forme acute, come l'ascesso parodontale, le attuali indicazioni suggerirebbero il ricorso all'antibiotico solo nei casi in cui la sintomatologia sia particolarmente severa e si tema per la diffusione della raccolta purulenta e per la salute generale del paziente [10,11] .…”
Section: Secondo Pipalova Et Al In Repubblicaunclassified
“…come un coadiuvante della terapia meccanica; risulta ingiustificata nel trattamento delle forme croniche [9,10] . Anche per alcune forme acute, come l'ascesso parodontale, le attuali indicazioni suggerirebbero il ricorso all'antibiotico solo nei casi in cui la sintomatologia sia particolarmente severa e si tema per la diffusione della raccolta purulenta e per la salute generale del paziente [10,11] .…”
Section: Secondo Pipalova Et Al In Repubblicaunclassified
“…characterized by a significant increase in generalized immune activation (1,2) and in mucosal inflammatory conditions such as periodontitis and gingivitis (3)(4)(5)(6). Some studies have reported an increased migration of inflammatory cells into the oral mucosa (7), whereas others have shown that levels of proinflammatory cytokines such as interleukin-6 (IL-6) (8-10) were significantly elevated during HIV infection.…”
Section: Hronic Human Immunodeficiency Virus (Hiv) Infection Ismentioning
confidence: 99%
“…Expected consequence of neglected oral health is likely tooth loss [33]. Clinical risk of spreading of late recognized and mistreated infection to the neighbouring soft tissues presents the issue of its own [34]. Furthermore, much anticipated consequence of authorities' lack of attention to this field of clinical medicine, is the so called boomerang effect.…”
Section: Discussionmentioning
confidence: 99%